85.0k views
0 votes
Prove t = 3.9 given: t+6.5=3t-1.3 with reason​

1 Answer

5 votes

Answer:

See below.

Explanation:

1) Subtract
t from both sides.


6.5=3t-1.3-t

2) Simplify
3t-1.3-t to
2t-1.3.


6.5=2t-1.3

3) Add
1.3 to both sides.


6.5+1.3=2t

4) Simplify
6.5+1.3 to
7.8.


7.8=2t

5) Divide both sides by
2.


(7.8)/(2) =t

6) Simplify
(7.8)/(2) to
3.9.


3.9=t

5) Switch sides.


t=3.9

Check the answer:


t+6.5=3t-1.3

1) Let
t=3.9.


3.9+6.5=3*3.9-1.3

2) Simplify
3*3.9 to
11.7.


3.9+6.5=11.7-1.3

3) Simplify
3.9+6.5 to
10.4.


10.4=11.7-1.3

4) Simplify
11.7-1.3 to
10.4.


10.4=10.4

Hence it can be proven that
t=3.9 is a result of the equation
t+6.5=3t-1.3.

Thank you.

User Branchgabriel
by
6.0k points